Print (“new blogpost”) - why digital HUMANISTS should learn the basic principles of coding - Karcher, Stefan (Interdisciplinary forum of digital textual sciences, 2019)
Back in my school days, I was not very good at learning new languages, but I had one goal: No matter what country I am in, I will not starve, because I will be...
Gesehen am 20.02.2019